18F-FDG PET/CT semi-quantitative parameters combined with SCC-Ag in predicting lymph node metastasis in stage I-II cervical cancer - Jiang, Cheng-Zhi; Zheng, Kai; Zhang, Yan-Yin; Yang, Jian; Ye, Hui; Peng, Xiang (Frontiers in Oncology, 2024)
Objective: To explore the value of 18F-fluordeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) metabolic parameters of primary tumor combined with squamous cell carcinoma antigen (SCC-Ag) in predicting lymph node metastasis (LNM) of cervical cancer (FIGO 2018 stage Ⅰ-Ⅱ). Materials and Methods: A total of 65 patients with stage Ⅰ-Ⅱ cervical cancer underwent 18F-FDG PET/CT were included in our study. Comparing the primary tumor 18F-FDG PET/CT semi-quantitative parameters and SCC-Ag between the LNM group and the non-LNM group. Logistic regression and receiver operating characteristic (ROC) were used to analyze the value of 18F-FDG PET/CT metabolic parameters and SCC-Ag in predicting LNM. Results: There were 14 and 51 patients were classified as having LNM and NLNM. The semi-quantitative parameters, including the maximum standardized uptake value (SUVmax), the mean standardized uptake value (SUVmean), the peak standardized uptake value (SUVpeak), the total lesion glycolysis (TLG), the metabolic tumor volume (MTV) of the tumor and SCC-Ag were all significantly higher in LNM than in NLNM (SUVmax, 16.07 ± 7.81 vs 11.19 ± 4.73, SUVmean, 9.16 ± 3.48 vs 6.29 ± 2.52, SUVpeak, 12.70 ± 5.26 vs 7.65 ± 3.26, MTV, 22.77 ± 12.36 vs 7.09 ± 5.21, TLG, 211.01 ± 154.25 vs 43.38 ± 36.17, SCC-Ag, 5.39 ± 4.56 vs 2.13 ± 2.50, all p<0.01). Logistic regression analysis showed that TLG was an independent predictor of LNM in stage Ⅰ-Ⅱ cervical cancer (OR 1.032, 95% CI 1.013-1.052, p<0.01). Moreover, the predictive value of TLG combined with SUVpeak and SCC-Ag increased and the area under the curve increased compared SUVpeak and SCC-Ag. Conclusion: 18F-FDG PET/CT semi-quantitative parameters and SCC-Ag have promise for assessing LNM in stage Ⅰ-Ⅱ cervical cancer. TLG of primary tumor provides independent and increasing values in predicting LNM in stage Ⅰ-Ⅱ cervical cancer.